2022
DOI: 10.1002/ppul.25937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical features of COVID‐19 infection in children with asthma and their healthy peers

Abstract: Aim We aimed to assess the impact of COVID‐19 on asthma exacerbations and to compare the severity of symptoms of SARS‐CoV‐2 infection of asthmatic children with those of healthy children. Methods The clinical course of COVID‐19 was compared among 89 children with asthma and 84 healthy children with age‐ and gender‐matched. Demographic factors, severity of asthma, duration of asthma, presence of atopy, type of treatment, and compliance to treatment in asthmatic children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 19 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…In the early stages of the COVID-19 pandemic, the effect of asthma on COVID-19 severity in children was examined in small studies, partially because of the lower prevalence of COVID-19 in children. 16) Whether asthma is a risk factor for COVID-19-associated hospitalization or severe COVID-19 remains controversial. Some studies have reported that asthma is not a risk factor for severe COVID-19 (Table 2).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 3 more Smart Citations
“…In the early stages of the COVID-19 pandemic, the effect of asthma on COVID-19 severity in children was examined in small studies, partially because of the lower prevalence of COVID-19 in children. 16) Whether asthma is a risk factor for COVID-19-associated hospitalization or severe COVID-19 remains controversial. Some studies have reported that asthma is not a risk factor for severe COVID-19 (Table 2).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Some studies have reported that asthma is not a risk factor for severe COVID-19 (Table 2). 16,17) However, others reported that children (12-17 years) with asthma are at higher risk of requiring hospitalization for COVID-19. 18) It has also reported that COVID-19 patients aged ≥16 years with asthma are more likely to require critical care (adjusted odds ratio [aOR], 1.20; 95% confidence interval [CI], 1.05-1.37), noninvasive ventilation (aOR, 1.36; 95% CI, 1.18-1.57), and oxygen supplementation (aOR, 1.33; 95% CI, 1.17-1.50) than those without asthma.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, some studies have shown poorer outcomes in children and adults with asthma 6,8,9 whereas others have detected a protective effect of asthma both for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and COVID‐19‐related death 10–12 . Therefore, the relationship between COVID‐19 and asthma is still unclear 13,14 . Moreover, in the pediatric setting, most studies are from high‐income countries, often with a small sample size, which may limit the generalizability of findings 15–17 …”
Section: Introductionmentioning
confidence: 99%